Governance of non-wood forest products in Russia and Ukraine: Institutional rules, stakeholder arrangements, and decision-making processes. (May 2020) - Stryamets, Nataliya; Elbakidze, Marine; Chamberlain, James; Angelstam, Per
Highlights: Governance of NWFPs includes sub-categories with economic, social, cultural, and ecological importance for a diverse range of stakeholders. Institutional rules in Ukraine and Russia for NWFPs are complex, overlap and unclear. Governance challenges are related to absence of law enforcement on sustainability of and access to NWFPs. Landscape approach initiatives respect customary rights and consider local contexts can be used to improve governance of NWFPs. Abstract: Aspects of governance of non-wood forest products (NWFPs) include institutional rules, stakeholder arrangements, and decision-making processes that govern production systems from access to resources, their use, and to markets. Compared with other forest products, few studies have investigated the governance of NWFPs in European post-socialistic countries transitioning from a planned to a market economy. This study compares institutional frameworks and stakeholder arrangements related to NWFPs in Russia and Ukraine using a case study approach. Both countries have a legacy of top-down forest government, state-owned forests, and rural communities with a long dependence on plant- and animal-based NWFPs. We analysed legal documents for NWFPs in each country and conducted expert interviews with stakeholders from the public, private, and civil sectors involved in the decision-making process of NWFPs. Institutional frameworks for NWFPs in both countries are complex, unclear, and overlap. Multiple legal documents contain restrictions regarding the extraction and sustainability of NWFPs. However, no special laws or policies are solely for NWFPs; all measures are included in legislation that regulates nature conservation and forest management. The government of both countries tends to overlook non-industrial forest use undertaken by marginal local communities, even if economic, social, and cultural values of NWFPs are relatively high for local and regional development. A misfit is observed between legal frameworks and forest companies' business policies with customary rights. This phenomenon caused a shift to introduce new stakeholder arrangements related to NWFPs as a special type of resource in areas where NWFPs are heavily used both for subsistence and for generating household income by local communities. Landscape approach initiatives such as model forests and biosphere reserves may empower local communities to find means to protect their rights, needs, interests, and values related to NWFPs.